Learning experience of creating architectural image on discipline “Semantic of Architecture” - Тroshkina O. (Theory and practice of design, 2015)
Article on the experience of teaching «Semantics of architecture» at the National Aviation University. Presented authoring exercises for reasons students the process of creating the architectural image.